2022
DOI: 10.1002/ijgo.14217
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of health‐related quality of life of women undergoing robotic surgery, laparoscopic surgery or laparotomy for gynecologic conditions: A cross‐sectional study

Abstract: Technological advances continue to revolutionize the surgical treatment of gynecologic conditions. 1 A recent innovation in the field of minimally invasive surgery is robot-assisted surgery, also known as robotic surgery, which offers the advantages of dimensional visual system, improved dexterity with wristed instrumentation, and elimination of hand tremors. The use of robotic equipment for gynecologic surgical procedures was first cleared by the US Food and Drug Administration in 2005. Since then, robotic su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
2
0
1
Order By: Relevance
“…Among 1,430 papers on robotic surgery research in obstetrics and gynecology in this research, we identified 64 papers on the quality of life. Kurt G et al' paper named "Comparison of health-related quality of life of women undergoing robotic surgery, laparoscopic surgery or laparotomy for gynecologic conditions: A cross-sectional study" demonstrated that women in the robotic group had better quality of life than that in laparoscopic or laparotomy group after gynecologic surgery (51).…”
Section: Principal Resultsmentioning
confidence: 99%
“…Among 1,430 papers on robotic surgery research in obstetrics and gynecology in this research, we identified 64 papers on the quality of life. Kurt G et al' paper named "Comparison of health-related quality of life of women undergoing robotic surgery, laparoscopic surgery or laparotomy for gynecologic conditions: A cross-sectional study" demonstrated that women in the robotic group had better quality of life than that in laparoscopic or laparotomy group after gynecologic surgery (51).…”
Section: Principal Resultsmentioning
confidence: 99%
“…En la consola de comando, el cirujano se sienta cómodamente donde controla la consola, el brazo del robot se mueve de manera flexible en tiempo real de acuerdo con los movimientos del cirujano sin demora entre el cirujano y el robot; así mismo, un visor estereoscopio de alta definición, puedes mostrar imágenes en 3D. (Cordero et al, 2022;Cohen et al, 2022;Kurt et al,2022) Además, esta consola también es muy útil porque el cirujano responsable de su manejo puede operar a distancia del paciente, eliminando así la necesidad de batas o guantes quirúrgicos, lo que se convierte en una ventaja ya que ahorra recursos hospitalarios. (Parks, 2022; Así mismo, Redondo et at., (2023) informan que los sistemas o aparatos en los que se utiliza da Vinci incluyen: abdominal, cardíaco, toracoscópico, ginecológico y urológico.…”
Section: Resultsunclassified
“…In a recent study, Kurt et al compared the health-related quality of life (HRQoL) of women who underwent robotic surgery, laparoscopic surgery, and laparotomy for gynecological disease [ 41 ]. The authors found a higher HRQoL after robotic surgery, which might be due to an early ambulation, a faster recovery, and a decrease in hospital stay reported in the robotic group, compared with the laparotomy or laparoscopy groups [ 41 ].…”
Section: Discussionmentioning
confidence: 99%